Picturing Midlife: Aging and the Limits of Narrative in Carol Shields’s Larry’s Party - Jamieson , Sara (Age, Culture, Humanities: An Interdisciplinary Journal, 2020)
This paper approaches Larry’s Party (1997) by Carol Shields as a detailed investigation into the political and representational issues at stake in writing about midlife by focusing on moments when the middle-aged Larry is describedas attempting to “visualize” his life (169). Highlighting Larry’s conviction that “his life is not ... a story” (267), his engagement with visual images raises questions about the centrality of narrative to how midlife is explained and imagined in contemporary literature and culture. Margaret Morganroth Gullette’s influential theorization of midlife and midlife fiction celebrates the sequential and teleological aspects of narrative as enabling a kind of life storytelling that characterizes the entry into middle age as progress toward an improved self. Questioning this conceptualization of a life as a linear, upward trajectory, Shields’s text foregrounds the assumptions about class implicit in the “progress novel” as Larry resists the devaluation of his working-class origins that would seem to accompany the imperative that he esteem his midlife self as better than his previous selves. Associating the fixity of the visual image with other non- narrative qualities such as touch, taste, and affective states characterized by stasis rather than momentum, Larry’s Party invites readers to question the cultural valorization of progress that continues to shape our assumptions about what it means to grow older.